Does Strategic Leadership Impact Competitive Advantage, Mediated by Diversification Strategy In the Manufacturing Industry? (International Journal of Scientific Research and Management (IJSRM), 2023)
The goal of this research is to conduct an analysis of the mediating role of diversification strategy in increasing competitive advantage, as well as the impact of strategic leadership, in the manufacturing industry located at Riau Island region, Indonesia, categorized as medium, large and export-oriented companies listed in the Riau Island’s Central Statistical Office 2021 directory. The method applied is quantitative research with Structural Equation Modelling (SEM) to test the hypothesis. Primary data were collected by sending questionnaires to 210 respondents as the representative of the manufacturing industry, by using purposive sampling, which was then analyzed using AMOS software. The study’s findings indicate that diversification strategy can operate as a significant and positive mediator in strategic leadership to achieve a competitive advantage, despite the fact that the direct effect test of the diversification strategy variable has no influence on competitive advantage. It may investigate adding other exogenous variables or applying dimensions such as cross-cultural leadership with a fixed population sample in the manufacturing industry, outside Riau Island, or in other countries for future research.